Effect of Treatment with Progestins and Antiplatelet Agents on IVF in Women with Adenomyosis and Recurrent Implantation Failure - Irina Pacu; Nikolaos Zygouropoulos; Giorgia Zampieri; Aida Petca; Mircea Octavian Poenaru; Cringu Antoniu Ionescu (Diagnostics)
Background: This prospective study aims to identify the effect of the dienogest 2 mg/day and aspirin 150 mg/day combined treatment for two months before frozen ET on the assisted reproduction outcome in women with adenomyosis and recurrent implantation failure (RIF). Methods: Patients were selected based on specific criteria and divided into two groups (with and without treatment). Preimplantation biochemical parameters and ultrasonographic features (endometrial thickness, uterine peristalsis, and junctional zone thickness) were compared with pregnancy rate in a non-natural cycle frozen embryo transfer technique. A comparison between the two study groups indicated an increased successful implantation rate and clinical pregnancy rate (25% vs. 7.4%). Results: These results were attributed to the reduced uterine peristalsis and the reduction in thickness of the junctional zone following treatment. Available data were limited due to the nature of the study though maximal effort was exerted for the selected patients between groups to be as demographically similar and free from other potential pathology that may affect the results. Conclusions: In conclusion, it appears that the above stated treatment improves outcomes in women with adenomyosis and RIF; the parameters used may provide an insight as to the reasons why this occurs, though an explanation of the molecular mechanisms is still elusive.